Amyloid aggregation of spin-labeled β-lactoglobulin. Part II: Identification of spin-labeled protein and peptide sequences after amyloid aggregation. (March 2021) - Lux, Jacqueline; Azarkh, Mykhailo; Fitzner, Laura; Keppler, Julia K.; Schwarz, Karin; Drescher, Malte; Steffen-Heins, Anja
Abstract: Site-directed spin labeling (SDSL) of natural β-lactoglobulin (β-lg) was established. Combined electron paramagnetic resonance (EPR) and mass spectrometric analysis following tryptic digestion demonstrated that spin labels bind site-specifically but are not directed to all five cysteine residues to various preferred and reproducible extents. MTSSL and iodoacetamido-proxyl spin label (IPSL) were 80 and 60% reliably bound to the H strand, respectively, and combined in one spectral component and buried in the protein core. After heat incubation at pH 2 and fractionation, all labeled side chains (peptides) were part of the amyloid and non-amyloid fractions, even if they could not detect amyloid structures. It was assumed that the IPSL-labeled side chains of peptides with Cys 160 from random coil were incorporated into small non-amyloid aggregates in non-polar environments. After heating at pH 3.5, a rearrangement of the previous α-helix was assumed to shift from the autonomous folding domain during partial unfolding, which improved the accessibility of β-sheets to the water/DMSO-environment. β-sheets were likely densely packed by the accumulation of intermolecular β-sheets, which suggests that amyloid-like structures can be formed from building blocks of the entire primary β-lg structure. Double electron-electron resonance (DEER) confirmed that the spatial distribution of labels within the amyloid-like fraction in a one-dimensional arrangement of the entire protein aggregates was similar to a string of pearls. Thus, SDSL of proteins containing several cysteine residues can be used to gain deep insights into the aggregation mechanism of proteins under food processing conditions. Graphical abstract: Image 1 Highlights: Both spin labels MTSSL and IPSL bind with different affinity to all five cysteines. MTSSL is most sensitive to changes in the arrangement of β-sheets. IPSL is most sensitive to changes in the random coil at position Cys 160 . At pH 3.5, the monomer-like β-lg aggregates in the form of a pearl chain. At pH 2, the labeled side chains are not incorporated into amyloid structures.